The Evolution of the Sal Natural Regeneration Technique and Subsidiary Silviculture in the Forests of Haldwani Division - Chopra, D. D. (Indian Forester, 1949)
The history of the forests if Haldwani division from the pre-British period has been narrated. Past systems of management under various working plans have been given. The mistakes made in the past, so far as they concern the natural regeneration of sal, have been pointed out. The role if the Middle storey kokat, which consists of inferior species of low marketability and useless shrubs, in nursing and securing the natural regeneration of sal has been pointed out. Future lines of management have been indicated.